2022
DOI: 10.1177/03331024221090204
|View full text |Cite
|
Sign up to set email alerts
|

P3 latency as a biomarker for the complexity of migraine with aura: Event-related potential study

Abstract: Background This study aimed to compare the P3 component between patients who have migraines with aura and healthy subjects, and to compare different subtypes of migraine with aura relative to the complexity of migraine aura. Methods Average Migraine Aura Complexity Score was calculated for each MwA patient. Visual oddball paradigm was used to elicit the P3 component. P3 amplitudes and latencies elicited from frequent and rare stimuli, as well as from difference wave, were compared with healthy subjects. Subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The preliminary results were comparable to the best reported in the literature, suggesting that AD detection could be automatically achieved through automated processing and commercial EEG systems. This research aligns with recent trends in combining non-invasive electrophysiological recordings with state-of-the-art signal processing and machine learning techniques to discover novel biomarkers for neurological disorders (Petrusic et al, 2022 ; Mitrović et al, 2023 ).…”
supporting
confidence: 74%
“…The preliminary results were comparable to the best reported in the literature, suggesting that AD detection could be automatically achieved through automated processing and commercial EEG systems. This research aligns with recent trends in combining non-invasive electrophysiological recordings with state-of-the-art signal processing and machine learning techniques to discover novel biomarkers for neurological disorders (Petrusic et al, 2022 ; Mitrović et al, 2023 ).…”
supporting
confidence: 74%
“…These differences were also highlighted in an evoked potential study where visual pathway activity was greater in complex aura sufferers than in pure visual aura, but both showed a deficient habituation to visual evoked potentials (Coppola et al, 2015). In a recent electrophysiological study, latency of the P3 event-related potential obtained with a visual oddball paradigm was significantly longer in MA+ patients than in MA or HC (Petrusic et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
“…For instance, Zhu et al (2019) demonstrated the efficacy of somatosensory evoked potentials for migraine classification. Petrusic et al (2022) emphasized the relevance of P3 latency, particularly when understanding the complexity of migraine with aura. Furthermore, another study by Petrusic et al (2021) presented findings on the N400 component in patients experiencing migraines with aura, hinting at the nuances of migraine pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the conventional electroencephalography (EEG) methods, various studies have utilized EEG event-related potentials, somatosensory evoked potentials, and visual evoked potentials in the pursuit of potential biomarkers (Hsiao et al, 2023;2021;Petrusic et al, 2021Petrusic et al, , 2022Zhu et al, 2019). For instance, Zhu et al (2019) demonstrated the efficacy of somatosensory evoked potentials for migraine classification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation